Optimization of thermophilic trans‐isoprenyl diphosphate synthase expression in Escherichia coli by response surface methodology. (14th March 2016) - Piccolomini, Angelica A.; Fiabon, Alex; Borrotti, Matteo; De Lucrezia, Davide
Abstract: We optimized the heterologous expression of trans ‐isoprenyl diphosphate synthase (IDS), the key enzyme involved in the biosynthesis of trans ‐polyisoprene. trans ‐Polyisoprene is a particularly valuable compound due to its superior stiffness, excellent insulation, and low thermal expansion coefficient. Currently, trans ‐polyisoprene is mainly produced through chemical synthesis and no biotechnological processes have been established so far for its large‐scale production. In this work, we employedD ‐optimal design and response surface methodology to optimize the expression of thermophilic enzymes IDS from Thermococcus kodakaraensis . The design of experiment took into account of six factors (preinduction cell density, inducer concentration, postinduction temperature, salt concentration, alternative carbon source, and protein inhibitor) and seven culture media (LB, NZCYM, TB, M9, Ec, Ac, and EDAVIS) at five different pH points. By screening only 109 experimental points, we were able to improve IDS production by 48% in close‐batch fermentation.